A dark inheritance : blood, race, and sex in colonial Jamaica - Newman, Brooke N. (Yale scholarship online., 2018)
A major reassessment of the development of race and subjecthood in the British Atlantic Focusing on Jamaica, Britain's most valuable colony in the Americas by the mid-eighteenth century, Brooke Newman explores the relationship between racial classifications and the inherited rights and privileges associated with British subject status. Weaving together a diverse range of sources, she shows how colonial racial ideologies rooted in fictions of blood ancestry at once justified permanent, hereditary slavery for Africans and barred members of certain marginalized groups from laying claim to British liberties on the basis of hereditary status.